SWEET POTATO (IPMOEA BATATAS L.) LEAF: ITS EFFECT ON PROLACTIN AND PRODUCTION OF BREAST MILK IN POSTPARTUM MOTHERS - Ima Candra Kusuma; Onny Setiani; Umaroh Umaroh; Noor Pramono; Melyana Nurul Widyawati; Suryati Kumorowulan (Belitung Nursing Journal, 2017)
Background: Sweet potato leaf is assumed to be one of alternative herbs that can increase breast milk production. However, there were no studies found in the literature that examine the sweet potato leaves to increase the levels of prolactin and milk production. Objective: To examine the effect of sweet potato (Ipomoea batatas L.) leaf on the level of prolactin and milk production in postpartum mothers. Methods: This was a quasi-experimental study with pretest-posttest design with control group, conducted on November 2016 to December 2016 in the Health Center (Puskesmas) of Boyolali I. Thirty respondents were selected using consecutive sampling, which were divided to be 15 respondents in intervention group and 15 respondents in control group. Enzyme-linked immunosorbent assay (ELISA) was used to measure prolactin levels, while breast milk production was measured based on the volume of breast milk and baby’s weight. Data were analyzed using Independent t-test and paired t-test. Results: Finding showed that there was a significant difference in prolactin levels between the intervention (270.43) and control group (156.28) after intervention with p-value 0.000, and a significant difference in breast milk production in terms of breast milk volume (intervention group 136.33; and control group 119) with p-value 0.028; and baby’s weight (intervention group 3030.3; and control group 2787.33) with p-value 0.000. Conclusion: There was a significant effect of sweet potato (Ipomoea batatas L.) leaf on the levels of prolactin and breast milk production. Thus, it could be suggested that sweet potato leaves should be considered to be one of alternative treatments for health care providers, especially for midwives to help breastfeeding mothers in increasing their breast milk production and prolactin levels. Further research is needed to examine all factors affecting breast milk production.